2018
DOI: 10.1038/s41598-018-28484-w
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Aqueous Humour Cytokine Profiles of Patients with Pachychoroid Neovasculopathy and Neovascular Age-related Macular Degeneration

Abstract: This study investigated the pathophysiological features of pachychoroid neovasculopathy (PNV) and neovascular age-related macular degeneration (nAMD) by analysing and comparing cytokine profiles in aqueous humour (AH) collected from 18 PNV, 18 nAMD and 11 control patients. Responses to intravitreal injection of aflibercept were also analysed in the PNV and nAMD groups. In the PNV group, vascular endothelial growth factor (VEGF)-A was significantly lower than in the nAMD group (p = 0.03) but was almost identica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 39 publications
3
66
0
1
Order By: Relevance
“…Although AH sampling is an invasive procedure, it is still accomplishable in humans in contrast to any of the tissue analyses, thereby supporting the diagnostic value of AH. The increased levels of pro-inflammatory cytokines in AH were previously found, not only in patients with pronounced intraocular inflammation (such as posterior uveitis), but also in individuals with AMD, diabetic retinopathy, macular edema, or glaucoma [39][40][41][42]. In the current study, we have demonstrated that the development of LIRD is accompanied by a chronic increase in the AH content of pro-inflammatory cytokine TNF-α.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Although AH sampling is an invasive procedure, it is still accomplishable in humans in contrast to any of the tissue analyses, thereby supporting the diagnostic value of AH. The increased levels of pro-inflammatory cytokines in AH were previously found, not only in patients with pronounced intraocular inflammation (such as posterior uveitis), but also in individuals with AMD, diabetic retinopathy, macular edema, or glaucoma [39][40][41][42]. In the current study, we have demonstrated that the development of LIRD is accompanied by a chronic increase in the AH content of pro-inflammatory cytokine TNF-α.…”
Section: Discussionsupporting
confidence: 74%
“…Indeed, alterations in malondialdehyde concentration and total antioxidant activity were found in AH of patients with glaucoma and exfoliation syndrome, as well as in animals with intraocular inflammation [35][36][37][38]. Furthermore, the increased levels of pro-inflammatory cytokines characterize AH of patients with AMD, diabetic retinopathy, macular edema, and glaucoma [39][40][41][42]. Meanwhile, alterations in oxylipin content of AH that are associated with LIRD and other retinal degenerative diseases remain mostly uninvestigated.…”
Section: Introductionmentioning
confidence: 99%
“…PNV ( Fig. 1) was diagnosed using the following criteria drawn from previous reports 2,3,11,27,28 : (1) type 1 CNV detected in either or both eyes; (2) no or only nonextensive drusen (total area 125 lm circle) or hard drusen ( 63 lm) in both eyes (Age-Related Eye Disease Study: Category 1, no AMD) 29 ; (3) CVH detected in the late phase of ICGA; (4) dilated choroidal vessels below the type 1 CNV detected by ICGA and SD-or SS-OCT; and (5) presence of CSC-or PPE-related RPE abnormalities independent of CNV lesions detected by FAF or a history of CSC.…”
Section: Diagnosis Of Acute Csc Chronic Csc and Pnvmentioning
confidence: 99%
“…2 Recently, we published the new findings that the cytokine profiles in aqueous humor (AH) of PNV and neovascular AMD are distinct, and that angiogenic factors and proinflammatory cytokines may play distinct roles in the pathogenesis of PNV and AMD. 11 It is well recognized that type 1 CNV occurs in eyes with long-term CSC, 12,13 but it can also occur in the absence of subretinal fluid. Some studies have speculated that the pathological progression of pachychoroid is conversion from acute CSC to chronic CSC or from PPE and eventually to PNV 14,15 ; however, not all patients with acute CSC develop chronic CSC, nor do all chronic CSC and PPE patients develop PNV.…”
mentioning
confidence: 99%
“…Two independent AMD specialists (M. Y. and H. H.) performed all of the diagnosis based on the criteria of pachychoroid spectrum disorders [18]. The supervising grader (N.…”
Section: Assessments Of Pachychoroid Spectrum and Choroidal Pachyvesselsmentioning
confidence: 99%